Assessing transition risks and financial implications of emission reduction in FMCG companies under Indonesia's ENDC framework - Kusumadewi, Dzikrina Almas (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: Indonesia has committed to limiting global temperature rise to below 2°C through ENDC, impacting emission-intensive sectors like FMCG. PT X faces transition risks from carbon surcharges and emission reductions to meet ENDC targets. This study analyzes these risks, showing the company must reduce emissions to avoid additional costs and comply with ENDC. Methods: This paper uses qualitative and quantitative methods to assess transition risks for FMCG companies, focusing on carbon emission reduction policies. The quantitative analysis involves calculating climate financial risks through scenario analysis, while the qualitative approach analyzes regulations and sustainability reports. The study uses a bottom-up approach to assess emissions in Scope 1 and 2 and applies sensitivity analysis to evaluate the financial impact of emission reduction policies. Findings: The scenario and sensitivity analysis shows that if PT X conducts operational activities in accordance with Business as Usual (BAU) for a 1.6% reduction in emissions, the company will experience an emission deficit (emissions above the ENDC target), which raises additional carbon costs of USD 21,199.91 tons CO2eq per year by the company. Meanwhile, in the scenario analysis and sensitivity analysis, the minimum level the company must reduce its emissions by 1.9% to get an emission surplus (emissions below the ENDC target). Conclusion: To reduce the impact of transition risk, companies can invest in the development of environmentally friendly technologies, and switch to renewable energy. The sale of carbon credits from surplus emissions can also be used by companies to cover carbon costs and mitigation actions. Novelty/Originality of This Study: This study lies in its application of climate financial risk analysis to assess the transition risks faced by Indonesia’s FMCG industry, providing a quantitative evaluation of emission reduction thresholds and their financial implications under the Enhanced Nationally Determined Contribution (ENDC) framework.